Identification of multiple ferritin genes in Macrobrachium nipponense and their involvement in redox homeostasis and innate immunity. Issue 89 (June 2019) - Tang, Ting; Yang, Zilan; Li, Jing; Yuan, Fengyu; Xie, Song; Liu, Fengsong
Abstract: Based on the transcriptome database, we screened out four ferritin subunit genes (MnFer2-5) from the oriental river prawn Macrobrachium nipponense, which encode two non-secretory and two secretory peptides. MnFer2 and 4 possess a strictly conserved ferroxidase site, and MnFer3 has a non-typical ferroxidase site. MnFer5 seems to be a number of ferritin families, which has a distinct dinuclear metal binding motif, but lacks an iron ion channel, a ferroxidase site and a nucleation site. Diverse tissue-specific transcriptions of the four genes indicate their functional diversity in the prawn. Among them, MnFer2 is mainly expressed in hepatopancreas and intestines, MnFer3 and 4 are predominantly expressed in gills, and MnFer5 is widely expressed in various tissues with high presence in intestines, hepatopancreas and haemocytes. The transcription of all the four MnFer genes can be strongly induced by doxorubicin, indicating the involvement of these ferritin subunits in protection from oxidative stress. Upon Aeromonas hydrophila infection, only MnFer5 is persistently up-regulated, while other subunits including MnFer2-4 are down-regulated during the early stage, followed by recovery and even a slight increase at 48 h post bacterial challenge. Moreover, the iron binding capacity of recombinant MnFer2 is also demonstrated in vitro. The E. coli expressing MnFer2 displays increased resistance to hydrogen peroxidase cytotoxicity. These results suggest a protective role of ferritins from M. nipponense in iron homeostasis, redox biology and antibacterial immunity and shed light on the molecule evolution of crustacean ferritin subunits. Highlights: Four new ferritin isoform transcripts MnFer2-5 are isolated from Macrobrachium nipponense. The transcription of all the four MnFers can be enhanced by doxorubicin. Only MnFer5 is persistently up-regulated upon bacterial infection. The iron binding capacity of recombinant MnFer2 is found in vitro . The E. coli expressing MnFer2 displays increased resistance to hydrogen peroxidase cytotoxicity.